Vinylferrocene copolymers based biosensors for phenol derivatives - Dursun, Fuat; Ozoner, Seyda Korkut; Demirci, Ali; Gorur, Mesut; Yilmaz, Faruk; Erhan, Elif (Wiley, 2012)
BACKGROUND: Newly synthesized composite films of P(glycidyl methacrylate85-co-vinylferrocene15)/Poly(glutaraldehyde)/ Polypyrrole [P(GMA85-co-VFc15)/PGA/PPy] and Poly(3-methylthienyl methacrylate85-co-vinylferrocene15)/Polypyrrole [P (MTM85-co-VFc15)/PPy] were used as matrices for tyrosinase based working electrodes. Direct covalent attachment of enzyme was carried out via the pendant epoxy groups of P(GMA85-co-VFc15) film, and the entrapment of enzyme was achieved for electrode containing P(MTM85-co-VFc15) film via electropolymerization of pyrrole in the presence of enzyme. The aim of the study is amperometric determination of various phenolics and investigation of the effect of interfacial interactions between enzyme and matrices on biosensor response. RESULTS: The lowest detection limit and the highest sensitivity for a P(GMA(85)-co-VFc(15)) based working electrode was found to be 0.113 mu mol L-1 for 4-methoxyphenol, 40 nA (mu mol L-1)-1 for pyrocatechol, respectively. Results showed that sensitivities were at least 8500-55000 times higher than the results in previous P(GMA-co-VFc) related studies. CONCLUSION: Facilitated electron transfer was achieved by means of mediator incorporated in conductive composites of VFc based redox copolymers. The effect was greater when enzyme was covalently bonded via epoxy groups due to the proximity of enzyme, mediator and electrode surface. Results showed that a multifunctional surface was provided on electrodes since the suggested copolymers could mediate an electrochemical reaction, and the multifunctional surface was capable of coating with conductive PPy. (C) 2011 Society of Chemical Industry
Keywords: vinylferrocene; glycidyl methacrylate; 3-methylthienyl methacrylate; conductive composites; immobilized tyrosinase; redox polymers